Economics by design : principles and issues - Collinge, Robert A; Ayers, Ronald M. (Upper Saddle River, N.J. Prentice Hall, 1997)
Contents: the economic journey; the power of prices; the energy of the marketplace; probing the public sector; aggregates for the big picture; the journey continues.
Includes bibliographical references and index.
Keywords: Quản trị kinh doanh